2020
DOI: 10.3389/fgene.2019.01329
|View full text |Cite
|
Sign up to set email alerts
|

The Epigenetic Connection Between the Gut Microbiome in Obesity and Diabetes

Abstract: Metabolic diseases are becoming an alarming health issue due to elevated incidences of these diseases over the past few decades. Various environmental factors are associated with a number of metabolic diseases and often play a crucial role in this process. Amongst the factors, diet is the most important factor that can regulate these diseases via modulation of the gut microbiome. The gut microbiome participates in multiple metabolic processes in the human body and is mainly responsible for regulation of host m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
108
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(114 citation statements)
references
References 135 publications
(145 reference statements)
0
108
0
6
Order By: Relevance
“…Our analysis of the α-diversity confirmed that letrozole impaired the richness and evenness of gut microbiota in rats and diminished the abundance of Ruminococcaceae. In addition, when we evaluated the changes in body weights of rats in each group, we demonstrated that the upregulation of the Firmicutes/ Bacteroidetes ratio was generally associated with obesity [25]. Although rat body weight in the letrozole group increased significantly, the Firmicutes/Bacteroidetes ratio in this group was not significantly different from the blank group.…”
Section: Discussionmentioning
confidence: 82%
“…Our analysis of the α-diversity confirmed that letrozole impaired the richness and evenness of gut microbiota in rats and diminished the abundance of Ruminococcaceae. In addition, when we evaluated the changes in body weights of rats in each group, we demonstrated that the upregulation of the Firmicutes/ Bacteroidetes ratio was generally associated with obesity [25]. Although rat body weight in the letrozole group increased significantly, the Firmicutes/Bacteroidetes ratio in this group was not significantly different from the blank group.…”
Section: Discussionmentioning
confidence: 82%
“…Alloprevotella have been found to improve obesity (Sharma, Li, Stoll, & Tollefsbol, 2020). The content of Parabacteroides was higher in the low-dose group (FL).…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with this, children who are treated with antibiotics in early childhood have a higher risk of allergies [87,88]. There is a lack of direct data on the impact of the microorganisms on the epigenetic processes in allergy, however, some data indicate that the alterations in function and composition of the gut microbiota are implicated in the pathogenesis of metabolic diseases, e.g., obesity and diabetes via the induction of epigenetic changes, such as DNA methylation, histone modifications and regulation by non-coding RNAs [89].…”
Section: Epigenetic Regulation Of Gene Expression In Pregnancy and Eamentioning
confidence: 99%